Electrical system for 41-storey Torre De Manila Bldg at Taft Avenue, Ermita, Manila, Philippines - Suelto, Edison R.
Torre de Manila is a condominium project of DM Consunji Inc. (DMCI). In June 2012, DMCI managed to secure a zoning permit that allows the company to build the Torre de Manila in a lot along Taft Avenue. The planned location of the building is behind the lot previously occupied by the Manila Jai Alai Building. The following month, the Manila city government under Mayor Alfredo Lim, granted a building permit to DMCI The electrical system design for this high rise building at Taft Avenue, Ermita, Manila, Philippines is consisting of 4 - Low Voltage Switchgear CLVSG) connected from - 7S0KVA, 34.SKV-Y/ 41SV-Y, 3-PHASE, 60HZ and synchronized to 4 - 7S0KVA, 400V-Y, 3-PHASE, 60HZ diesel generator set.